Review of the ecotoxicological effects of emerging contaminants to soil biota - Gomes, Ana R. (2017)
In recent years, emerging contaminants (e.g. pesticides and their metabolites, pharmaceuticals, personal and house care products, life-style compounds, food additives, industrial products and wastes, as well as nanomaterials) have become a problem to the environment. In fact, the cumulative use of a panoply of chemical substances in agriculture, industrial activities, in our homes and in health care services has led to their recent appearance in detectable levels in soils, surface, and groundwater resources, with unpredictable consequences for these ecosystems. Few data exist regarding the toxicity and potential for bioaccumulation in biota. When available, data were obtained only for some representatives of the main groups of chemical substances, and for a limited number of species, following non-standard protocols. This makes difficult the calculation of predicted no effect concentrations (PNEC) and the existence of sufficient data to set limits for their release into the environment. This is particularly concerning for the soil compartment, since only recently the scientific community, regulators, and the public have realised the importance of protecting this natural resource and its services to guarantee the sustainability of terrestrial ecosystems and human well-being. In this context, this review paper aims to identify the major groups of soil emerging contaminants, their sources, pathways and receptors, and in parallel to analyse existing ecotoxicological data for soil biota.